2019
DOI: 10.1002/ar.24069
|View full text |Cite
|
Sign up to set email alerts
|

Differential Changes in the Number and Morphology of the New Neurons after Chronic Infusion of Wnt7a, Wnt5a, and Dkk‐1 in the Adult Hippocampus In Vivo

Abstract: In the adult hippocampus of many mammals, a particular microenvironment in the neurogenic niche regulates the proliferation, self-renewal, and differentiation of neuronal stem cells. In this proliferative niche, a variety of molecules provide a finely regulated molecular signaling that controls stem cell properties. During development, Wnt signaling has been implicated in cell fate determination and proliferation, in the establishment of cell polarity, as well as a cue for axonal growth and dendrite orientatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…We determined that genetic knockdown of Wnt5a in the dentate gyrus decreased the generation of adult‐born neurons. In line with this result, it was recently shown that chronic infusion of Wnt5a on the hippocampus of adult rats induced an increase in the density of Dcx+ neurons . The effect of Wnt5a knockdown on neurogenesis is likely mediated by the strong decrease that we observed in neuronal differentiation, since there were no changes in proliferation or total number of newborn cells.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We determined that genetic knockdown of Wnt5a in the dentate gyrus decreased the generation of adult‐born neurons. In line with this result, it was recently shown that chronic infusion of Wnt5a on the hippocampus of adult rats induced an increase in the density of Dcx+ neurons . The effect of Wnt5a knockdown on neurogenesis is likely mediated by the strong decrease that we observed in neuronal differentiation, since there were no changes in proliferation or total number of newborn cells.…”
Section: Discussionsupporting
confidence: 89%
“…In line with this result, it was recently shown that chronic infusion of Wnt5a on the hippocampus of adult rats induced an increase in the density of Dcx+ neurons. 70 The effect of Wnt5a knockdown on neurogenesis is likely mediated by the strong decrease that we observed in neuronal differentiation, since there were no changes in proliferation or total number of newborn cells. 75 In these cells, the canonical ligand Wnt1 is required for DA specification, and Wnt1 and noncanonical Wnt5a cooperate to promote midbrain DA neurogenesis in vivo.…”
Section: Discussionmentioning
confidence: 76%
“…A similar effect was observed when Wnt5a was reduced in cultured AHPs, in which neuronal differentiation and morphological development of the derived neurons were reduced, while treatment with Wnt5a had the opposite effect ( Arredondo et al, 2020 ). In agreement, chronic infusion of Wnt5a ligand into the adult rat hippocampus increased the number of immature neurons and altered their pattern of neurite outgrowth ( Ortiz-Matamoros and Arias, 2019 ). In cultured AHPs, Wnt5a activated CamKII, PKC and JNK ( Arredondo et al, 2020 ), and activated AP1 and c-jun in differentiated but not proliferative AHPs ( Schafer et al, 2015 ), indicating that Wnt5a triggers activation of non-canonical Wnt signaling cascades.…”
Section: Wnt Signaling In the Regulation Of Adult Hippocampal Neurogementioning
confidence: 71%
“…Wnt7a knockout mice showed fewer NPCs, which exhibited lengthened cell cycles and a reduced cell cycle reentry, and also showed impaired neuronal differentiation ( Qu et al, 2013 ). On the contrary, chronic infusion of Wnt7a directly into the rat hippocampus increased the number of immature neurons ( Ortiz-Matamoros and Arias, 2019 ). Wnt7a knockdown in NSCs reduced the expression of Cyclin D1, while when NSCs were induced to differentiate into neurons Wnt7a knockdown reduced mRNA levels of neurogenin 2 (Ngn2).…”
Section: Wnt Signaling In the Regulation Of Adult Hippocampal Neurogementioning
confidence: 99%
“…Two branches of the Wnt signalling pathway influence adult neurogenesis progression in the hippocampus. Canonical signalling affects both the early and the late stages of the neurogenic progression and dictates proliferation, neuronal specification, dendritic growth and spine formation (Lie et al, 2005;Kuwabara et al, 2009;Qu et al, 2013;Heppt et al, 2020), while non-canonical signalling influences maturation (Schafer et al, 2015;Ortiz-Matamoros and Arias, 2019;Arredondo et al, 2020). In the canonical pathway, secreted Wnt ligands bind to a complex of frizzled (FZD) receptors and co-receptors, phosphorylating Dishevelled that in turn recruits the beta-catenin (β-catenin) destruction complex formed by glycogen synthase kinase 3 beta (GSK3B), casein kinase 1α (CK1α), APC (Adenomatosis Polyposis Coli) and Axin among other proteins, allowing β-catenin accumulation and nuclear translocation (Clevers and Nusse, 2012).…”
Section: Introductionmentioning
confidence: 99%